Effect of triacontanol on the pharmacokinetics of docetaxel in rats associated with induction of cytochrome P450 3A1/2. (July 2014) - Deng, Shuhua; Wang, Chunfeng; Zhang, Wei; Gao, Wenchao; Fan, Ali; Zhang, Qiuyang; Zhang, Yongjie; Liu, Qingwang; Li, Ning; Liu, Qi; Zhao, Jie; Li, Cuiyun; et al.
Abstract 1. <?ri?>Triacontanol was confirmed to have a potential anti-cancer effect, the aim was to assess whether the co-administration of triacontanol alters the exposure of docetaxel via inducing hepatic CYP3A1/2 activity. The concentration of docetaxel in rats pretreated with triacontanol for seven successive days was determined, and the expression levels of CYP3A protein and mRNA were analyzed by the western blot and real time polymerase chain reaction (RT-PCR) technique, respectively. 2. <?ri?>The concentrations of docetaxel in rats pretreated with triacontanol were decreased, with 61.5%, 61.9% decrease in AUC0–24h and 65.7%, 54.9% reduction in Cmax (120 and 180 mg kg−1, respectively) compared with the control. Hepatic clearance of docetaxel was enhanced in vitro and in vivo at dosage of 120 and 180 mg kg−1, and CYP3A activity was up-regulated by measuring the formation rate of 1-hydroxymidazolam. Triacontanol preferentially induced protein expression level of CYP3A2 in a dose-dependent manner and of CYP 3A1 at dosage of 120 and 180 mg kg−1. The mRNA expression of CYP3A1 was moderately different with the western blot results, but the trends appeared similar. CYP3A2 mRNA level was not markedly affected by triacontanol. 3. <?ri?>The significant triacontanol–docetaxel interaction was largely due to the induction of CYP3A1/2, which brought useful information in the clinical therapy when the combination is administered in human.